Use of the Internet and Digital Devices Among People With Severe Mental Ill Health During the COVID-19 Pandemic Restrictions - Spanakis, Panagiotis; Heron, Paul; Walker, Lauren; Crosland, Suzanne; Wadman, Ruth; Newbronner, Elizabeth; Johnston, Gordon; Gilbody, Simon; Peckham, Emily (Frontiers in Psychiatry, 2021)
Background: Restrictions due to the COVID-19 pandemic have led to everyday reliance on digitalisation of life, including access to health care services. People with severe mental ill health (SMI – e.g., bipolar or psychosis spectrum disorders) are at greater risk for digital exclusion and it is unknown to what extent they adapted to online service delivery. This study explored use of the Internet and digital devices during the pandemic restrictions and its association with physical and mental health changes. Methods: 367 adults with an SMI diagnosis completed a survey (online or offline) and provided information on access to Internet connection and devices, internet knowledge, online activities, and barriers to using the Internet. They also self-reported changes in mental and physical health since the beginning of the pandemic restrictions. Results: During the pandemic restrictions 61.6% were limited or non-users of the Internet. The majority had access to the Internet and digital devices but around half reported knowledge deficits. Most common activities were accessing information and entertainment (88.9%), staying in touch with friends and families (84.8%), and purchasing goods (other than food) (84.3%). Most common barriers were finding the Internet ‘not interesting’ (28.3%) or ‘too difficult’ (27.9%), as well as ‘security concerns’ (22.1% to 24.3%). Using the Internet ‘a lot’ (vs 'just a bit or not at all') during the pandemic was associated with younger age (18-30: Adj ORs 4.76; 31-45: 6.39; Ps < .001; vs 66+), having a diagnosis of bipolar disorder (compared to psychosis; Adj OR = 3.88, P < .001), or reporting a decline in mental health (compared to no decline; Adj OR = 1.92, P = .01). Conclusion: Most people with SMI were limited or non-users of the Internet during the pandemic, which seems to be mainly attributable to lack of interest and skills, rather than lack of devices or connectivity. Older adults with psychosis should be the focus of interventions to support digital engagement in people with SMI.